Organizational rhetoric in the prospectuses of elite private schools: unpacking strategies of persuasion - McDonald, P.; Pini, Barbara; Mayes, Robyn (Routledge, 2012)
The way in which private schools use rhetoric in their communications offers important insights into how these organizational sites persuade audiences and leverage marketplace advantage in the context of contemporary educational platforms. Through systemic analysis of rhetorical strategies employed in 65 ‘elite’ school prospectuses in Australia, this paper contributes to understandings of the ways schools’ communications draw on broader cultural politics in order to shape meanings and interactions among organizational actors. We identify six strategies consistently used by schools to this end: identification, juxtapositioning, bolstering or self-promotion, partial reporting, self-expansion, and reframing or reversal. We argue that, in the context of marketization and privatization discourses in twenty-first-century western education, these strategies attempt to subvert potentially threatening discourses, in the process actively reproducing broader economic and social privilege and inequalities.